KEANEKARAGAMAN JENIS VEGETASI HUTAN MANGROVE DESA SUNGAI KUPAH KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Darwati, Herlina; Herlina, Lina; Widhanarto, Ganjar Oki (Universitas Tanjungpura, 2024)
Sungai Kupah village, Sungai Kakap District, Kubu Raya Regency which still has a mangrove forest area. A part of the mangrove area is currently in the development stage of a newly opened natural tourism spot and managed by tourism awareness group and local community. This study aims to obtain information on species diversity in the mangrove forest area in Sungai Kupah Village, Sungai Kakap District, Kubu Raya Regency. Data collection was obtained based on the checkered path method and placed purposively. Vegetation data observed adjusted to plan stratification, namely saplings and seedlings. The are 7 types of vegetation that can be found, namely Achantus ilicifolius, Acrosticum aureum, Avicennia alba, Avicennia marina, Sonneratia caseolaris, Morinda citrifolia, Nypa fruticans. The species diversity index (H